Malaria prevention in highland Kenya: Indoor residual house-spraying vs. insecticide-treated bednets - Guyatt, H.L.; Corlett, S.K.; Robinson, Timothy P.; Ochola S.A.; Snow, R.W. (Wiley, 2002)
This study compares the effectiveness and cost-effectiveness of indoor residual house-spraying (IRS) and insecticide-treated bednets (ITNs) against infection with Plasmodium falciparum as part of malaria control in the highlands of western Kenya. Homesteads operationally targeted for IRS and ITNs during a district-based emergency response undertaken by an international relief agency were selected at random for evaluation. Five hundred and ninety homesteads were selected (200 with no vector control, 200 with IRS and 190 with ITNs). In July 2000, residents in these homesteads were randomly sampled according to three age-groups: 6 months–4 years, 5–15 years, and > 15 years for the presence of P. falciparum antigen (Pf HRP-2) using the rapid whole blood immunochromatographic test (ICT). The prevalence of P. falciparum infection amongst household members not protected by either IRS or ITN was 13%. Sleeping under a treated bednet reduced the risk of infection by 63% (58–68%) and sleeping in a room sprayed with insecticide reduced the risk by 75% (73–76%). The economic cost per infection case prevented by IRS was US$ 9 compared to US$ 29 for ITNs. This study suggests that IRS may be both more effective and cheaper than ITNs in communities subjected to low, seasonal risks of infection and as such should be considered as part of the control armamentarium for malaria prevention.